The intrauterine contraceptive device. - Barwin, B. N. (1978)
This presentation brings into perspective the most recent information on intrauterine contraceptive devices. A comprehensive review of the literature is presented in a manner meaningful to the clinician. The advantages and disadvantages of this method of contraception, the problems that arise and the recommended methods of management are discussed. An updated review of the literature with regard to bleeding, pain, expulsion of the device, infection, uterine perforation and pregnancy is also presented.